Messy entanglements: research assemblages in heart transplantation discourses and practices. Issue 1 (28th September 2017) - Shildrick, Margrit; Carnie, Andrew; Wright, Alexa; McKeever, Patricia; Jan, Emily Huan-Ching; De Luca, Enza; Bachmann, Ingrid; Abbey, Susan; Dal Bo, Dana; Poole, Jennifer; El-Sheikh, Tammer; Ross, Heather
Abstract : The paper engages with a variety of data around a supposedly single biomedical event, that of heart transplantation. In conventional discourse, organ transplantation constitutes an unproblematised form of spare part surgery in which failing biological components are replaced by more efficient and enduring ones, but once that simple picture is complicated by employing a radically interdisciplinary approach, any biomedical certainty is profoundly disrupted. Our aim, as a cross-sectorial partnership, has been to explore the complexities of heart transplantation by explicitly entangling research from the arts, biosciences and humanities without privileging any one discourse. It has been no easy enterprise yet it has been highly productive of new insights. We draw on our own ongoing funded research with both heart donor families and recipients to explore our different perceptions of what constitutes data and to demonstrate how the dynamic entangling of multiple data produces a constitutive assemblage of elements in which no one can claim priority. Our claim is that the use of such research assemblages and the collaborations that we bring to our project breaks through disciplinary silos to enable a fuller comprehension of the significance and experience of heart transplantation in both theory and practice.